Pyruvate Kinase M2 and Cancer: The Role of PKM2 in Promoting Tumorigenesis - Zahra, Kulsoom; Dey, Tulika; Ashish; Mishra, Surendra Pratap; Pandey, Uma (Frontiers in oncology, 2020)
Pyruvate kinase plays a pivotal role in regulating cell metabolism. The final and rate-limiting step of glycolysis is the conversion of Phosphoenolpyruvate (PEP) to Pyruvate, which is catalyzed by Pyruvate Kinase. There are four isomeric, tissue-specific forms of Pyruvate Kinase found in mammals: PKL, PKR, PKM1, and PKM2. PKM1 and PKM2 are formed bya single mRNA transcript of the PKM gene by alternative splicing. The oligomers of PKM2 exist in high activity tetramer and low activity dimer forms. The dimer PKM2 regulates the rate-limiting step of glycolysis that shifts the glucose metabolism from the normal respiratory chain to lactate production in tumor cells. Besides its role as a metabolic regulator, it also acts as protein kinase, which contributes to tumorigenesis. This review is focused on the metabolic role of pyruvate kinase M2 in normal cells vs. cancerous cells and its regulation at the transcriptional level. The review also highlights the role of PKM2 as a potential diagnostic marker and as a therapeutic target in cancer treatment.